827. Does Patient Location (Rural or Urban) influence risk factors and incidence rate for 30-day readmission after gram positive pneumonia?. (31st December 2020) - Kunnumpurath, Anthony; Mehta, Neal; Khan, Shoaib; Kamoga, Gilbert-roy
Abstract: Background: In the US, pneumonia is the most common cause of a hospital admission. Prior analysis has shown that nearly one in six patients will have an all-cause 30-day readmission. Given the disparities in access to healthcare between rural and urban settings, we sought to see if patient location influenced the incidence rate for 30-day readmission after treatment for Gram Positive Pneumonia. Methods: We utilized Agency of Healthcare Research and Quality's (AHRQ) 2014 Nationwide Readmission Database to identify index admissions with a principal diagnosis of Gram Positive Pneumonia (ICD-9 codes 482.3, 482.31, 482.32, and 482.39 for streptococcus and 482.40, 482.41, 482.42, and 482.49 for staphylococcus). The 2013 NCHS Urban-Rural Classification System was used to classify if originating from an urban or rural location. Applicable admissions were all adults (age >= 18) from January 1 to November 30, 2014. Patients who died during index admission and those with missing covariates were excluded. All-cause readmissions within 30-days of an index admission were analyzed. Predictors for readmission were determined using a multivariable logistic regression model. Results: A total of 8, 130 patients met criteria for inclusion of which 1, 631 (20.06%) were readmitted (all-cause) within 30-days. There was no statistically significant difference in readmission between patients from a rural (18.7%) or urban (20.4%) location. The statistically significant predictors for readmission for patients from a rural location were those admitted on a weekend (OR: 1.41, CI: 1.04-1.90), discharged to short term hospital (OR: 2.70, CI: 1.18-6.19) or AMA (OR: 6.53, CI: 1.46-29.10), and those with a LOS between 7 and 14 days (OR: 1.48, CI: 1.10-2.00). For patients from an urban location, statistically significant predictors were those admitted on a weekend (OR: 1.17, CI 1.02-1.34), discharged AMA (OR: 2.89, CI: 1.74-4.78), LOS between 7 and 14 days (OR: 1.19, CI: 1.03-1.37) and those with CKD (OR: 1.20, CI: 1.03-1.39). Conclusion: The risk factors for readmission after Gram Positive Pneumonia for patients from a rural and urban location are similar. More research is needed to develop interventions for those who are at risk for readmission after Pneumonia to reduce future morbidity and mortality. Disclosures: All Authors : No reported disclosures